1996
DOI: 10.1159/000462104
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the Monocyte Chemiluminescent Response to Anti-D- Sensitized Red Cells by FcγRI-Blocking Antibodies Which Ameliorate the Severity of Haemolytic Disease of the Newborn

Abstract: Luminol-enhanced chemiluminescence (CL) may be used to measure the metabolic response of human monocytes to red cells sensitized by anti-D. The functional activity of maternal anti-D when measured in this way correlates with the severity of haemolytic disease of the newborn (HDN) in D-positive fetuses. Occasionally, however, women with levels of functionally active anti-D predictive of moderate to severe HDN may deliver D-positive babies with unexpectedly mild disease. In the current study we have shown that s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2000
2000
2000
2000

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
2
0
0
Order By: Relevance
“…2 and 3). This hypothesis was independently confirmed in studies on mothers and their newborns with HDN (138,139). Our group came to the same conclusion in a multicenter study on more individuals without, in contrast to Dooren et al (138) and Shepard et al (139), selecting the cases by immunological criteria of the causative Rhesus antibodies.…”
Section: Placental Fc Receptorssupporting
confidence: 85%
See 1 more Smart Citation
“…2 and 3). This hypothesis was independently confirmed in studies on mothers and their newborns with HDN (138,139). Our group came to the same conclusion in a multicenter study on more individuals without, in contrast to Dooren et al (138) and Shepard et al (139), selecting the cases by immunological criteria of the causative Rhesus antibodies.…”
Section: Placental Fc Receptorssupporting
confidence: 85%
“…Our group came to the same conclusion in a multicenter study on more individuals without, in contrast to Dooren et al (138) and Shepard et al (139), selecting the cases by immunological criteria of the causative Rhesus antibodies. Contrary to the findings of Dorren et al (138) and in agreement with those of Shepard et al (139), we found that the ameliorating antibodies were primarily specific for HLA A, B, and C (140). Maternal HLA antibodies also could be protective against other detrimental antibodies of the mother, e.g., to fetal platelet antigens causing the fetal or neonatal alloimmune thrombocytopenia or passive autoimmune thrombocytopenia, and to neutrophil granulocyte antigens causing the respective alloimmune neutropenia of the child.…”
Section: Placental Fc Receptorssupporting
confidence: 82%